ГРОМОВНИКОТ И НЕГОВИТЕ КАМЕНИ ИЛИ БОЖЈИ СТРЕЛИ׃ ГРОМОТ И МОЛЊАТА: споредбена анализа кај јужнословенските народи (Filološke studije, 2019)
The basic aim of the research of this propound paper is the study of Slovenian Thunder man and his wеapons – thunder and lighting. In addition, a compared analysis will be made between the Macedonian and other South Slovenian people based upon the used terminology and native beliefs. The goal is to prove, that even one single token can be a significant proof for relations between different and distant individuals, community and culture.